2013
DOI: 10.1016/j.jss.2013.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Pepsin concentrations are elevated in the bronchoalveolar lavage fluid of patients with idiopathic pulmonary fibrosis after lung transplantation

Abstract: Background Aspiration of gastroesophageal refluxate has been implicated in the pathogenesis of idiopathic pulmonary fibrosis (IPF) and the progression of bronchiolitis obliterans syndrome after lung transplantation. The goals of the present study were to identify lung transplant patients at the greatest risk of aspiration and to investigate the causative factors. Materials and methods From September 2009 to November 2011, 252 bronchoalveolar lavage fluid (BALF) samples were collected from 100 lung transplant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 39 publications
(48 reference statements)
0
33
0
Order By: Relevance
“…Numerous studies have documented increased levels of pepsin in BAL of patients following lung-transplantation[35,78,79,84]. In a small study by Ward et al[79], pepsin was present in the BAL of all lung allografts, while not detected in the control group.…”
Section: Background and Pathophysiologymentioning
confidence: 99%
“…Numerous studies have documented increased levels of pepsin in BAL of patients following lung-transplantation[35,78,79,84]. In a small study by Ward et al[79], pepsin was present in the BAL of all lung allografts, while not detected in the control group.…”
Section: Background and Pathophysiologymentioning
confidence: 99%
“…7,8,12,[14][15][16][17] This is supported by the lower pH or elevated concentrations of pepsin in bronchoalveolar lavage in patients with IPF. 18,19 Esophageal manometry in patients with GERD and IPF shows decreased lower esophageal sphincter pressure (LESP) with normal esophageal function, and further decreased upper esophageal sphincter pressure than LESP. 6,20 These findings may explain why typical symptoms such as heartburn are uncommon in patients with IPF.…”
Section: Introductionmentioning
confidence: 99%
“…While proton‐pump inhibitor (PPI) therapy is widely used for symptomatic GER, the effect of acid suppression on pulmonary outcomes in IPF patients has not been definitively established, although a few studies have shown some benefits . Studies evaluating broncho‐alveolar lavage of patients with IPF demonstrated an increase in both pepsin and bile acids, suggesting that non‐acid reflux may also play a role in the pathogenesis or progression of IPF. Furthermore, Linden et al .…”
Section: Introductionmentioning
confidence: 99%